Optimization of laparoscopic ureteral repair with a buccal graft in case of its extended strictures and obliterations - A. A. Volkov; N. V. Budnik; O. N. Zuban (Исследования и практика в медицине)
Purpose of the study. Currently, laparoscopic technique has become widely used in the treatment of extended strictures and obliterations of the ureter. The use of minimally invasive approaches will also be relevant for such a relatively new operation as buccal ureteroplasty. In the literature, there are isolated publications devoted to this technique. The aim of this study was to study the results of our own experience of laparoscopic ureteral reconstruction using a buccal graft.Patients and methods. We observed 5 patients – 2 men and 3 women, at the age of 30–62 years. All patients have already been operated on the urinary tract, of these, in four patients, the urinary tract was drained with a nephrostomy or internal ureteral stent. Two patients underwent replacement ureteroplasty with tubularized buccal graft, and three patients underwent augmentation ureteroplasty with buccal graft using the onlay method.Results. All operations in this group were carried out without conversions. The average length of the ureteral defect was 4.9 cm (4.0–6.0 cm). The patients did not have severe complications in the postoperative period according to the ClavienDindo classification. One patient underwent treatment for exacerbation of chronic pancreatitis; one man experienced ureteral stent migration, which required restentation. The follow-up period was 1–15 months; one woman developed unextended ureteral restenosis, which was eliminated by endoureterotomy and ureteral stenting. At the moment, all patients are spared from permanent urinary drains, they do not have upper urinary tract obstruction. Conclusion. All operations in this group were carried out without conversions. The average length of the ureteral defect was 4.9 cm (4.0–6.0 cm). The patients did not have severe complications in the postoperative period according to the Clavien-Dindo classification. One patient underwent treatment for exacerbation of chronic pancreatitis; one man experienced ureteral stent migration, which required restentation. The observation period for the patients was 1–15 months, one woman developed short ureteral restenosis, which was eliminated by endoureterotomy and ureteral stenting. At the moment, all patients do not have permanent urinary drains, violations of the urodynamics of the upper urinary tract were not revealed in them.